Edukasi Dan Implementasi Tentang Etika Dan Keselamatan Lalu Lintas Di SMK Negeri 3 Takalar - Hamdan Kadir; Ahmad Jihad; Fadillah Nuraulia Tahir; Irsyan Nur (PT.Mantaya Idea Batara, 2023)
Abstract: The progress of transportation for today's society has positive and negative impacts. On the one hand, it facilitates community mobilization and on the other hand, the number of vehicles on the road and the facilities available are not commensurate, which can result in congestion on the road. In addition, there are many traffic drivers who do not comply with traffic rules so that road accidents sometimes occur which can be fatal. Types of violations that often occur are not wearing a helmet and even doing freestyle while driving. Ironically, the drivers who often commit these violations are teenagers. This problem is also found in partner areas, namely at SMKN 3 Takalar, so that community service is carried out in the form of counseling related to how to educate students about traffic safety and pay attention to the ethics that need to be applied when driving a vehicle. This activity was carried out on December 7, 2022. In this counseling, a pre-test and post-test were also given as indicators of achieving the objectives of this counseling.